Systemic blockade of D2-like dopamine receptors facilitates extinction of conditioned fear in mice - Ponnusamy, Ravikumar (Cold Spring Harbor Laboratory Press, 2005)
Extinction of conditioned fear in animals is the explicit model of behavior therapy for human anxiety disorders, including panic disorder, obsessive-compulsive disorder, and post-traumatic stress disorder. Based on previous data indicating that fear extinction in rats is blocked by quinpirole, an agonist of dopamine D2 receptors, we hypothesized that blockade of D2 receptors might facilitate extinction in mice, while agonists should block extinction, as they do in rats. One day after fear conditioning mice with three pairings of a white noise conditional stimulus (CS) with moderate footshock, we injected the D2 antagonist, sulpiride, the D2 agonist, quinpirole, or vehicle, just before repeated CS presentations to generate extinction. We assayed fear by measuring behavioral freezing during extinction presentations and then drug-free during CS presentations 1 d later. We found that sulpiride injections before extinction training facilitated extinction memory 24 h later, while quinpirole partially blocked extinction memory compared with vehicle-injected controls. Notably, sulpiride treatment yielded significant extinction after spaced CS presentations, which yield no extinction at all in vehicle-treated mice. These findings suggest that dopamine D2-mediated signaling contributes physiological inhibition of extinction, and that D2 antagonists may be useful adjuncts to behavior therapy of human anxiety disorders.